New Caledonian species misplaced in Horaeomorphus Schaufuss belong in Heterotetramelus Franz (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2021)
Horaeomorphus Schaufuss is an easily identifiable genus of Stenichnini, predominantly distributed in the Australasian realm. Many scydmaenines occurring in other regions, however, have been misplaced in Horaeomorphus, and therefore the true distribution of this genus remains unclear. In previous studies several new genera were established for Australian species misplaced in Horaeomorphus, and a few species misplaced in Euconnus Thomson, Stenichnus Thomson, and Syndicus Motschulsky were transferred to Horaeomorphus. Three species that inhabit New Caledonia were placed in this genus: Horaeomorphus australis Franz, H. baloghi Franz, and H. novaecaledoniae Franz. Examination of these taxa revealed that none of them was conspecific with the SE Asian type species of Horaeomorphus. Three new combinations are proposed: Heterotetramelus (s. str.) australis (Franz) comb. n., Heterotetramelus (s. str.) baloghi (Franz) comb. n., and Heterotetramelus (s. str.) novaecaledoniae (Franz) comb. n.; each species is redescribed.